Contents and the language used in graffiti: A case of Kathmandu Valley - Paudel, Jagadish; Neupane, Pratiksha (Journal of NELTA, 2019)
Graffiti is prevalent in modern cities across the world. It represents a range of issues and ideas, and its meaning can be interpreted socially, culturally, and politically. It features distinct forms of language. Using Multimodal Discourse Analysis (MDA) approach, this study analyses the contents, language and linguistic features of 44 graffiti arts found in the Kathmandu Valley to interpret the meanings of the graffiti. The results of this study reveal multiple issues such as culture, politics, gender discrimination and violence against women. The use of language and linguistics in the graffiti seems distinct in terms of word choice, syntactic structure, and rhetorical devices. It was found that the graffitists used multiple modes such as sign, symbol, color, words with images and stylish writing structures. The study will be of great importance to the researchers who want to analyze the language of graffiti and interpret the meanings they denote and to contribute to the body of existing literature on linguistic studies of graffiti. It is also useful for course designers and educators as they can incorporate graffiti in the courses and use them as resource materials in the classroom.